Peran Teknologi dalam Pembelajaran Matematika: Analisis Studi Literatur - Fadila, Nanda Nur; Fuat; Khoiri, Miftahul; Sukmawati, Afifatus (Al-'Adad: Jurnal Tadris Matematika, 2025)
This study aims to examine the role of technology in mathematics learning through a literature review. The main problem highlighted is the low motivation and achievement of students in mathematics, often due to traditional teaching methods that are less engaging. Using a qualitative approach with a literature review design, data were collected from relevant scientific articles published in national and international journals indexed by SINTA and Scopus. The findings indicate that technology plays a vital role in supporting mathematics education. Various interactive learning media, such as interactive multimedia, GeoGebra, Wordwall, augmented reality (AR), QuizWhizzer, and 3D printing technology, have been proven effective in helping students grasp abstract mathematical concepts by making them more concrete. Additionally, technology can enhance students’ motivation, critical thinking skills, and problem-solving abilities, leading to more meaningful learning experiences. For teachers, technology facilitates the design of more varied, interactive, and student-centered lessons, thus supporting their role as facilitators. However, the implementation of technology still faces challenges, particularly regarding infrastructure limitations and teachers’ readiness to operate technology-based learning media. Therefore, optimizing the use of technology in mathematics education is essential to help students achieve competencies relevant to 21st-century needs.